Assessment of the Level of Pain Intensity and the Level of Anxiety Treated as State and Trait in Patients with Osteoarthritis of the Limbs - Jadwiga Kuciel-Lewandowska; Michał Kasperczak; Łukasz B. Lewandowski; Małgorzata Paprocka-Borowicz (Pain Research and Management)
Introduction. Osteoarthritis of the musculoskeletal system is accompanied with chronic pain which is the main factor in mood lowering, causing anxiety. Rehabilitation conducted in the framework of spa therapy and outpatient care aims at eliminating or reducing pain and improving physical fitness. Pain relief is an expected phenomenon because it improves the quality of life. Aim of the study. The aim of the study was to evaluate the effect of rehabilitation in the spa and in outpatient clinic on the level of pain and anxiety in patients with degenerative joints and disc disease. Material and methods. The study included a comprehensive treatment conducted in the spa and in outpatient clinic. Observation included 120 persons with disorders of the musculoskeletal system treated in the spa Przerzeczyn-Zdrój. The second group of patients was treated in the rehabilitation clinic. The examinations were performed before and after treatment. The scope of the observations included self-evaluation of anxiety treated as a state and a trait, the level of intensity of pain, medical history, and sociodemographic background interview. In the observations, there were VAS scale and State Trait Anxiety Inventory STAI used. Result. As a result of the spa therapy and therapy performed in an outpatient clinic, there was an improvement in lowering the level of pain and anxiety noted. Conclusions. 1. Spa therapy and treatment performed in an outpatient clinic reduce the level of pain and anxiety in patients with degenerative disease of the musculoskeletal system. 2. It was found that the therapy conducted in the spa was more effective in lowering the level of pain and anxiety. This trial is registered with NCT03405350.